Enhanced durability of a cost-effective perovskite-carbon catalyst for the oxygen evolution and reduction reactions in alkaline environment. (16th November 2017) - Alegre, C.; Modica, E.; Rodlert-Bacilieri, M.; Mornaghini, F.C.; Aricò, A.S.; Baglio, V.
Abstract: The design of a bifunctional air electrode able to carry out both the oxygen reduction and evolution reactions in an alkaline environment is essential for the progress of new-generation energy conversion and storage devices. Alkaline systems allow the use of non-noble metals, which favors a considerable reduction of the system cost. In this work, a cost-effective perovskite, La0.6 Sr0.4 Fe0.8 Co0.2 O3, has been investigated as bifunctional catalyst in a 6 M KOH alkaline solution. The perovskite was mixed with an experimental carbon black, characterized by a graphitic structure and a specific surface area of 220 m 2 g −1 . The perovskite-carbon composite was compared to a Pd/C catalyst (employing the same carbon black as support). Generally, bifunctional catalysts are subjected to high electrochemical potentials, particularly during the oxygen evolution. In order to assess the stability of the bifunctional catalyst, several accelerated degradation tests were performed. Results proved that the perovskite-carbon composite showed good performance for both reactions, in particular for the oxygen evolution. Furthermore, it also presented enhanced stability vs. Pd/C when subjected to degradation tests, maintaining a constant potential over time, even working at high current densities (80 and 125 mA cm −2 ). This material is envisaged as a very promising bifunctional catalyst, in particular in terms of durability. Highlights: La0.6 Sr0.4 Fe0.8 Co0.2 O3 was investigated as bifunctional catalyst for air electrode. Oxygen reduction and evolution reactions were assessed in alkaline media. La0.6 Sr0.4 Fe0.8 Co0.2 O3 proved to be an effective and stable bifunctional catalyst.